Management Practices in Hospitals and Their Impact on Employees - Sahdev, Anu (Digital Repository of Theses, 2024)
The paramount theme of this thesis is how hospital administration impacts the sector’s development. The focus is placed on staff management and providing patients with access to promising medical facilities. The two most vital facets considered are how the hospital handles its resources and how the management impacts the staff. As a result, the business thrives, and the healthcare industry witnesses pristine developments. This research focuses on the Procedures, planning, organizing, controlling, and overseeing of government and private hospitals. Working and guiding the people especially, in NGOs that how to behave in the hospital and understand the management of the hospital. Likewise, the examination of how the hospital behaves towards the poor, how the administration addresses the circumstances, and what modifications they accomplish for the benefit of the patients in the hospital sector at the J.J. Institute of Medical Science has been observed. This research is distinctive and endeavors to cope with a segment of society that is underserved. This research has investigated how additional satisfactory hospitality can be extended to those in the lower socioeconomic strata. This research has analyzed data from private and government hospitals and captures the quality of management practices based on staff surveys and management. Trained underprivileged people and saw the impact on employees in government hospitals also studied the model of NHS hospital. This research has presented a novel approach to measuring the effectiveness of managerial practices in the healthcare industry. Encourage management methods that are patient-centered since this can boost employee job satisfaction because employees can see how their work impacts patients. Further research should focus on indirect aspects of management and its impact on employees and try to adopt the NHS model of hospital and its intricacies. Awareness of what to do, if any illness happens, through interactive sessions, easy-to-understand booklets, etc. Also conducted the health training session with the hospital management, and employees on how to deal with patients so that they don’t feel overwhelmed by the process and can be patiently treated.